2005
DOI: 10.1021/jf0502810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ascorbic Acid and Dehydration on Concentrations of Total Phenolics, Antioxidant Capacity, Anthocyanins, and Color in Fruits

Abstract: The purpose of this investigation was to report on the total phenolics, anthocyanins, and oxygen radical absorbance capacity (ORAC) of strawberry, peach, and apple, the influence of dehydration and ascorbic acid treatments on the levels of these compounds, and the effect of these treatments on fruit color. Results showed that fresh strawberry had the highest levels for total phenolics [5317.9 mg of chlorogenic acid equivalents (CAE)/kg], whereas lower levels were found in fresh apple and peach (3392.1 and 1973… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
56
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 16 publications
12
56
1
2
Order By: Relevance
“…This is because dipping in ascorbic acid solution inhibits browning enzymes such as PPO (Piližota and Šubaric', 1998). This result is in agreement with the experimental result reported by Rababah et al (2005) who found that the samples (apple, peach and strawberry) dipped in ascorbic acid solution had signifi cantly higher L-value than the un-pretreated samples. Blanching could also inhibit PPO (Piližota and Šubaric', 1998;Trirattanapikul and Phoungchandang, 2012) but the blanched sample became darker with a slight loss of yellowness as manifested by lower Land b-values.…”
Section: Colorsupporting
confidence: 93%
See 1 more Smart Citation
“…This is because dipping in ascorbic acid solution inhibits browning enzymes such as PPO (Piližota and Šubaric', 1998). This result is in agreement with the experimental result reported by Rababah et al (2005) who found that the samples (apple, peach and strawberry) dipped in ascorbic acid solution had signifi cantly higher L-value than the un-pretreated samples. Blanching could also inhibit PPO (Piližota and Šubaric', 1998;Trirattanapikul and Phoungchandang, 2012) but the blanched sample became darker with a slight loss of yellowness as manifested by lower Land b-values.…”
Section: Colorsupporting
confidence: 93%
“…In the case of ginger slices dipped in ascorbic acid solution, it was found that TPC was similar to that of fresh ginger. This result is in agreement with the fi nding of Rababah et al (2005), who found an insignifi cant diff erence in TPC values between sample pretreated by dipping in 0.1% (w/v) ascorbic acid solution (for 2 min) and the un-pretreated sample. In contrast, Rocha and Morais (2005) found an increase in TPC in apple cubes a er 5 min of dipping in 0.75% (w/v) ascorbic acid solution.…”
Section: Total Phenolic Contentsupporting
confidence: 92%
“…On the contrary, ascorbic acid and total sugar showed negative correlations with the colour of persimmon powder (r = −0.729 and −0.685, p < 0.01, respectively). Ascorbic acid was found to reduce the redness (a*) and the yellowness (b*) colour values of strawberry, peach, and apple puree (Rababah et al 2005), which was in line with our results. The impact of ascorbic acid on colour loss has been reported intensively, however, the corresponding mechanism still remained unclear.…”
Section: Correlation Of Powder Recovery Of Spray Drying With Sugar Ansupporting
confidence: 92%
“…Fresh edible part of Kiwi fruit pulp (5 ± 0.2 g) from each cultivar were homogenized in 25 mL of extraction solvent (Acetone: methanol: water: acetic acid; 40: 40: 20: 1) as described by Rababah et al (2005) with some modification. The homogenate was transferred into a 50 mL centrifuge tube and incubated at 60 0 С in a water bath for 1 h. Samples were centrifuged at 13,000 × g for 15 min at 4 0 С, then filtered through Whatman filter paper no 1 and diluted to a final volume of 50 mL.…”
Section: Determination Of Total Polyphenols (Tp)mentioning
confidence: 99%